EFEK BULAN JANUARI (JANUARY EFFECT) DAN EFEK HARI LIBUR (HOLIDAY EFFECT) STUDI EMPIRIS DI BURSA EFEK INDONESIA - Baharsah, Ab Syarifudin (Jurnal Manajemen Update, 2017)
This research is a quantitative research study which will examine the existence of events January effect and Holiday efect in Indonesia Stock Exchange 2011-2015. In this study, researchers will test whether there is a difference of return and trading volume activity in January with a month other than January, and will be to investigate whether there are differences in return and trading volume activity before and after Holiday effect. The data used in this research Â is the daily stock price data to calculate daily returns and stock trading volume data on a holiday effect which only uses the data five days before the event and five days after the event. The sample used in this study are 50 companies listed in the Index Kompas 100 2011-2015. Paired samples t-test and one way ANOVA test is used to test the hypothesis of the first and second, while for the third and fourth test hypotheses just using a paired samples t-test. The result of the four hypotheses were tested did not show the existence of both the January effect and holiday effect in the Indonesia Stock Exchange. Keywords: January effect, holiday effect, returns, trading volume activity